Original articleThe protective action of alpha-tocopherol on the white matter lipids during moderate hypoxia in rats - Kapelusiak-Pielok, Magdalena; Adamczewska-Goncerzewicz, Zofia; Dorszewska, Jolanta; Grochowalska, Alina (Folia Neuropathologica, 2005)
Hypoxia and ischemia acting on the brain cause alterations of the level of lipids and sterols. Famile 3.0-3.5-month-old rats were used for the experiment. They were given alpha-tocopherol in the dose of 11.43 mg/kg of body weight through seven days, then underwent hypoxia (7% of oxygen in the breathing mixture) and myelin was isolated in four times after experiment: 4, 24 hours, 14 days and 2 months after experiment. Three lipids groups were isolated that are neutral lipids, galactolipids and phospholipids. They were quantitatively analyzed with spectrophotocolorimetry. The obtained results indicate that vitamin E administration to animals does not cause significant changes of brain lipids levels. However, alpha-tocopherol administred before moderate hypoxia balances the concentrations of lisophosphatidylcholine and phosphatidylinositide and cerebrosides with control level 2 months after experiment. Vitamin E changes in concentration of the myelin neutral lipids. Vitamin E administered before experimental moderate hypoxia stabilizes some membrane lipids and could be used in brain hypoxia.